Differential effects of monophosphoryl lipid A on expression of suppressor T cell activity in lipopolysaccharide-responsive and lipopolysaccharide-defective strains of C3H mice. - Ekwunife, F S (1991)
Lipopolysaccharide (LPS)-responsive and LPS-defective strains of C3H mice did not differ in the capacity to make an antibody response to type III pneumococcal polysaccharide or in the degree of thymus-derived suppressor cell (Ts) activity generated following exposure to type III pneumococcal polysaccharide. However, treatment with monophosphoryl lipid A (MPL) abolished the expression of Ts function in LPS-responsive but not LPS-defective mice. Since this effect was elicited by different preparations of MPL, it appears to be a general property of MPL mediated by direct action of MPL on activated Ts.